2019
DOI: 10.1590/1980-5373-mr-2018-0123
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Polypropylene Adhesion by Kraft Lignin Incorporation

Abstract: Low surface energy and poor adhesion are well-known characteristics of polypropylene (PP). Surface treatments such as plasma, corona, and laser are usually applied to overcome these limitations. However, current studies highlight the incorporation of hydrophilic or amphiphilic polymers into hydrophobic low-surface-energy polymers as an alternative for increasing surface energy and thus improving adhesion. Lignin could be a promising amphiphilic polymer for use in increasing surface energy. In this work, PP/kra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…The mechanical property deterioration that was verified for PU_30HKL_PC is probably due to the emergence of a second phase in this concentration, which was revealed and discussed in the DMA results. The interfaces between the primary and the lignin‐rich secondary phase can act as stress concentration sites, which can lead to premature failure and thus could possibly explain the reduction of ultimate tensile strength and elongation at break for the PU_30HKL_PC sample 57,58 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical property deterioration that was verified for PU_30HKL_PC is probably due to the emergence of a second phase in this concentration, which was revealed and discussed in the DMA results. The interfaces between the primary and the lignin‐rich secondary phase can act as stress concentration sites, which can lead to premature failure and thus could possibly explain the reduction of ultimate tensile strength and elongation at break for the PU_30HKL_PC sample 57,58 …”
Section: Resultsmentioning
confidence: 99%
“…The interfaces between the primary and the ligninrich secondary phase can act as stress concentration sites, which can lead to premature failure and thus could possibly explain the reduction of ultimate tensile strength and elongation at break for the PU_30HKL_PC sample. 57,58…”
Section: Uniaxial Tensile Testmentioning
confidence: 99%
“…In that work, optimal amounts of lignin were proved to secure the stress transferring between the phases promoting the strengthening of the composite. Additionally, other authors suggested the use of lignin as binder between the fibers and hydrophobic matrices [ 40 , 41 ]. In general, there seems to be a balance between the lignin content, which provides a good dispersion of the reinforcement inside the matrix, and the hydroxyl groups in cellulose, ensuring a good interfacial bonding with the coupling agent.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, partial replacement of Polypropylene by Lignin is economically and ecologically gained attention for versatile applications [ 35 ]. Lignin combination in the Polypropylene matrix at various loading levels was presented [ 36 , 37 , 38 , 39 ]. The development of novel synthetic strategies to simplify miscible polymer/lignin blends with massive efforts has been made to recognize the potential advantages of Lignin for the growth and develop new thermoplastic polymer mixture [ 40 ].…”
Section: Introductionmentioning
confidence: 99%